Factors Associated With Non-suicidal Self-Injury in Chinese Adolescents: A Meta-Analysis - Fan, Yang-yang; Liu, Jing; Zeng, Yan-yan; Conrad, Rachel; Tang, Yi-lang (Frontiers in Psychiatry, 2021)
Non-suicidal self-injury (NSSI) in adolescents is an increasing public health problem in China. We conducted a meta-analysis of studies on NSSI in Chinese adolescents (between 10-19 years) to examine factors associated with NSSI. Twenty-five papers including 30 separate studies with 186,447 participants were included for analysis. The results from a random-effects model showed a weak, but significant overall prediction of NSSI (OR=1.734). There were significant associations between the following seven factors and NSSI (ranking by the effect sizes, in descending order): adverse life events (OR=2.284), negative coping style (OR=2.040), problematic internet use (OR=2.023), Sleep disturbance (OR=1.734), traumatic experiences (OR =1.728), problematic parent-child relationship (OR=1.585), mental health problem (OR=1.578). Additionally, NSSI sample type moderated these effects. These findings highlight factors significantly associated with NSSI in Chinese adolescents. Parent-child relationship and mental health of the only children and left-behind children in China deserve more attention.